Designing Energy Supply Chains: Dynamic Models for Energy Security and Economic Prosperity. Issue 6 (2nd March 2017) - Rafique, Raza; Mun, Kwon Gi; Zhao, Yao
Abstract : Many developing countries suffer severe energy deficiencies despite their ample reserves of resources – the so‐called predicament of " resource rich, energy poor ." A leading driver is the energy‐economy cycle, where poor economic status, inefficient utilization of limited budget, and energy deficiency reinforced each other and led these countries into a spiral of economic downfall. How to turn this cycle around? It is a classic question but not well answered in the energy policy/economics literature and barely studied in the operations management literature. We apply supply chain design and location optimization models to address the unique features of the energy sector in these countries and present a new class of mathematical models for designing coal‐fired energy supply chains. The model captures the interaction among different parts of an integrated energy supply chain, the unique economics of power transmission such as yield losses, the political issues associated with equity, and the dynamic interaction among energy consumption, economy and budget. The model attempts to answer the classic question by determining the optimal and politically feasible ways to build up an energy supply chain under limited budgets for energy security and economic prosperity. Applying the model to Pakistan's recent energy crises, we show that the solutions can significantly outperform the government's plan by reducing the energy gaps faster, boosting the economy stronger with less greenhouse gas emissions. We develop insights as to how an energy supply chain should be built up strategically for developing countries, and how various system parameters may affect the results.